SENIOR HIGH SCHOOL STUDENTS’ PERCEPTION OF MOBILE LEARNING PEDAGOGICAL FEATURES USED FOR ENGLISH SUBJECT - Rahman Khalik, Muhammad Fathur; Astuti, Sri ((JELE) Journal Of English Language and Education, 2024)
This study aimed to investigate senior high school students’ perceptions toward the dimensions of m- learning pedagogical features for English subject, and the differences of the students’ perceptions toward the dimensions based on their gender. This study was a descriptive survey study involving 324 senior high school students from eight senior high schools in Kabupaten Soppeng, Sulawesi Selatan. The participants were selected using snowball sampling in which the samples were chosen with the help of each school principal who forwarded the link of the online survey to every student in their schools. The data were collected using a valid and reliable questionnaire which was adapted from iPAC scales. The data analysis involved in this study was confirmatory factor analysis (CFA), descriptive statistics and multivariate analysis of variance (MANOVA). The results of the CFA revealed that m-learning pedagogical features for English subject in senior high school was reflected by three dimensions namely, personalization, authenticity, and collaboration. Moreover, based on the descriptive statistics, senior high school students in Kabupaten Soppeng, Sulawesi Selatan, showed positive perception toward the use of m-learning pedagogical features for English subject. Further, MANOVA shows that there was no significant difference of the students’ perceptions toward the dimensions of m-learning pedagogical features for English subject based on gender (p = .218).